Targeted cell therapy for partial-thickness cartilage defects using membrane modified mesenchymal stem cells by transglutaminase 2. (August 2021) - Li, Hui; Jin, Yuhong; Zhao, Yu; Li, Wenjing; He, Zihao; Zhang, Qingxi; Huang, Hesuyuan; Lin, Jianjing; Chen, Yuyang; Xing, Dan; Du, Yanan; Lin, Jianhao
Abstract: Unlike full-thickness cartilage defects (FCD), partial-thickness cartilage defects (PCD) may still have residual healthy cartilage tissue, and therefore, the conventional clinical treatments such as microfracture and autologous chondrocyte implantation (ACI) are so traumatic that they may not be the suitable therapies for PCD. Although intra-articular injection of mesenchymal stem cells (MSCs) is a minimally invasive treatment, its therapeutic efficacy is markedly limited due to anoikis caused by failure of cell colonization in the injured area. By modifying a functional polypeptide on the MSC plasma membrane and exploiting the high expression of transglutaminase 2 (TGase2) in the regions of injured cartilage, we achieved targeted recognition and capture of modified MSCs by injured articular chondrocytes (ACs). In the in vitro co-culture model, MSCs improved the function of injured ACs and enhanced the chondrogenic differentiation potential of MSCs. Results of in vitro study also revealed that the activation of the AKT/mTOR signaling pathway may play an important role in the treatment of injured ACs by MSCs. Further, membrane-modified MSCs exhibited a better therapeutic effect than wide-type MSCs in a rabbit model of PCD. Thus, this unique cell membrane modification strategy provides a new cell-based therapeutic approach for the early treatment of articular cartilage defects and other joint diseases.